Stand structure is more important for forest productivity stability than tree, understory plant and soil biota species diversity - Wang, Tao; Dong, Lingbo; Liu, Zhaogang (Frontiers in Forests and Global Change, 2024)
The stability of forest productivity is management goal to sustain ecosystem services for an expanding human population and in the face of global change. Evidence from theoretical, observational and experimental studies has demonstrated that higher biodiversity tends to promote forest productivity stability. The majority of these studies, however, have focused solely on tree diversity, neglecting the potentially important role of understory plant and soil biodiversity. In this study, we explain the effect of tree, understory woody and herbaceous plant, soil biota (fauna, fungi and bacteria) species diversity on the forest productivity and its time stability across Northeast China (covering 145 million hectares). Importantly, we explored the eight stand structure variables for forest productivity stability relationship between tree, understory plant, and soil biota species diversity and productivity stability. Our results showed no significant direct impact of understory plant, soil fungi and bacteria species diversity on the stability of the forest ecosystem, tree species diversity indirectly affects productivity stability by directly influencing stand structure, whereas soil fauna species diversity indirectly influences stability through its relationship with tree species diversity. Stand structure is more important than tree and soil fauna species diversity for forest productivity stability. Specifically, increasing crown height (CH) from its minimum to maximum value leads to a substantial gain of 20.394 in forest productivity stability. In contrast, raising tree and soil fauna species diversity (α-Tree and α-Fauna) from its minimum to maximum value results in a modest reduction of only 0.399 and 0.231 in forest productivity stability. Overall, they raise awareness regarding the ecological risks associated with large-scale biotic homogenization under future climate change and forest management practices.